Assessing plastic waste management performance: Insights from the waste management performance index - Prabawati, Anindita; Frimawaty, Evi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In 2015, Indonesia was the second-largest contributor to marine debris worldwide, with an estimated 0.48-1.29 million metric tons of marine waste. In Jakarta, the marine waste generation reached 303.6 tons per day. Government programs such as JAKSTRADA and JAKSTRANAS aim to reduce plastic waste by 30% and manage 70% of waste by 2025. These policies promote circular economy-based waste management, but household participation remains low, with only 1.6% contributing to the 3R (reduce, reuse, recycle). Methods: This study employs both quantitative and qualitative approaches to measure the performance of circular economy-based plastic waste management in Jakarta. The population includes both formal and informal sectors, such as waste banks and waste pickers. Data is analyzed using the Waste Management Performance Index (IKPS) from SIPSN and BPS, comparing plastic waste management achievements with JAKSTRADA targets up to 2025. Findings: In Jakarta, per capita waste generation is 0.7 kg/day, mainly organic and plastic. Despite a decline in collected waste, plastic waste is rising. Management follows Law No. 18/2008 and Presidential Regulation No. 97/2017, involving formal (TPS 3R, waste banks) and informal (collectors, vendors) sectors. The informal sector aids recycling by collecting plastic from inaccessible areas. JAKSTRADA targets waste reduction, handling, and recycling until 2025. The Waste Management Performance Index (IKPS) evaluates policy, effectiveness, and efficiency. Conclusion: Waste management in Central Jakarta is still low with an index of 26% and a recycling rate of 12.6%, despite achieving 99.98% of the collaboration target. Novelty/Originality of this article: This study highlights the integration of formal and informal sectors in plastic waste management in Central Jakarta, emphasizing the use of the Waste Management Performance Index (IKPS) to assess policy effectiveness and recycling progress toward JAKSTRADA targets.